Understanding Occupation Patterns in Lisbon’s Docked Bike Sharing System - Ribeiro, Margarida Maria Garcia Sequeira (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence